Langevin Equations with Generalized Proportional Hadamard–Caputo Fractional Derivative. (8th December 2021) - Barakat, M. A.; Soliman, Ahmed H.; Hyder, Abd-Allah
Abstract : We look at fractional Langevin equations (FLEs) with generalized proportional Hadamard–Caputo derivative of different orders. Moreover, nonlocal integrals and nonperiodic boundary conditions are considered in this paper. For the proposed equations, the Hyres–Ulam (HU) stability, existence, and uniqueness (EU) of the solution are defined and investigated. In implementing our results, we rely on two important theories that are Krasnoselskii fixed point theorem and Banach contraction principle. Also, an application example is given to bolster the accuracy of the acquired results.